Multiple-seller and multiple-buyer spectrum sharing model in cognitive radio-based wireless sensor network - Yuxing Mao; Tao Cheng; Huiyuan Zhao; Na Shen (International Journal of Distributed Sensor Networks)
As the use and scale of wireless sensor networks has grown, the lack of transmission spectrum has become a key factor affecting wireless sensor network quality of service. An effective solution is to collect unused spectrum from primary users (i.e. licensed users) and use that spectrum for wireless sensor networks. In this article, for a cognitive radio-based wireless sensor network, a spectrum sharing strategy between primary users and clusters is proposed. First, as a secondary user (i.e. an unlicensed user), the base station plays a Bertrand game with the monopolists (the primary users) to gain spectrum access on behalf of the clusters. Then, the base station allocates the spectrum band to the cluster heads using the ant colony optimization–based multiple knapsack problem. After obtaining the spectrum, each cluster head programs its nodes’ spectrum according to a timing sequence. Simulation results show that the Bertrand game model is a good choice for determining spectrum pricing and that the ant colony optimization–based multiple knapsack problem algorithm is an efficient way to allocate spectrum dynamically.